Configuring the project management office: case of an innovation industrial company - I. V. Katunina (Real Economics Publishing House, 2018)
Project management development in various industries and spheres of activity has caused a variety of forms and functions of project management offices. This has caused the need to develop an approach to the configuration of the office of a company. The research object – an innovative industrial company – predetermined the need to form a project management office as a center of management consulting. The study was carried out on the basis of the case-study methodology, which combined the documents analysis, assessment of the project management maturity and survey methods.It proposes and approves the approach to designing the project office configuration based on the assessment of the level of organizational and technological project management maturity. The in-depth study of the industrial innovation company made it possible to disclose the main components and connections in the system «innovation – project management (project office) – consulting». As a result, the set of functions of the project management office is determined, and in particular, the content of the consultancy function in the process of the current activity within the innovative industrial company (process consulting).